Messung und Abrechnung im Bereich der Elektromobilität - Graf Neidhardt von Gneisenau, Carsten (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The work presents the legal framework for the measurement and billing of charging current to end customers. The starting point for this is the perspective of the underlying business process („meter-to-cash process“). On the basis of this process perspective the requirements of energy law, calibration law and data protection law, which must be observed for a legally compliant process, are discussed for various supply constellations. In addition to the term of the end consumer, which plays a central role in the legal conformity of the process, the focus is also on the link to the technical contexts in view of the digitalization and automation of the process.